The Peroxisome Proliferator-Activated Receptor Gamma System Regulates Ultraviolet B-Induced Prostaglandin E2 Production in Human Epidermal Keratinocytes - Raymond L. Konger; Kellie Clay Martel; Danielle Jernigan; Qiwei Zhang; Jeffrey B. Travers (PPAR Research)
Studies using PPARγ agonists in mouse skin have suggested that peroxisome proliferator-activated receptor gamma (PPARγ) is irrelevant to cutaneous photobiology. However, in several epithelial cell lines, ultraviolet B (UVB) has been shown to induce the nonenzymatic production of oxidized phospholipids that act as PPARγ agonists. UVB is also a potent inducer of prostaglandin E2  (PGE2) production and COX-2 expression in keratinocytes and PPARγ is coupled to increased PGE2 production in other cell lines. In this current study, we demonstrate that PPARγ agonists, but not PPARα or PPARβ/δ agonists, induce PGE2 production and COX-2 expression in primary human keratinocytes (PHKs). Importantly, PPARγ agonist-induced COX-2 expression and PGE2 production were partially inhibited by the PPARγ antagonist, GW9662, indicating that both PPARγ-dependent and -independent pathways are likely involved. GW9662 also suppressed UVB and tert-butylhydroperoxide- (TBH-) induced PGE2 production in PHKs and intact human epidermis and partially inhibited UVB-induced COX-2 expression in PHKs. These findings provide evidence that PPARγ is relevant to cutaneous photobiology in human epidermis.